Bioerosion of inorganic hard substrates in the Silurian of Estonia (Baltica). (2nd April 2016) - Vinn, Olev; Toom, Ursula
Abstract: Carbonate hardgrounds are unevenly distributed in the Silurian of Estonia, with only three bioeroded hardgrounds in the Telychian and one in the late Pridoli. There seem to be no trends in the bioerosion intensities and ichnotaxonomical diversity in the Silurian of Estonia. Only Trypanites occurs in the hardgrounds of the Silurian of Estonia and ichnological diversity of bioeroded organic hard substrates, containing Trypanites, Palaeosabella and Osprioneides is higher than inorganic substrates. The small number of bioeroded inorganic substrates could indicate that these substrates were probably less important than the organic hard substrates for the development of seafloor ecological niches in the Silurian of Estonia. The average bioerosion intensities of the hardgrounds are relatively high, but not unusual for the Silurian.